Adipose tissue: between the extremes. (16th June 2017) - Vegiopoulos, Alexandros; Rohm, Maria; Herzig, Stephan
Abstract: Adipose tissue represents a critical component in healthy energy homeostasis. It fulfills important roles in whole‐body lipid handling, serves as the body's major energy storage compartment and insulation barrier, and secretes numerous endocrine mediators such as adipokines or lipokines. As a consequence, dysfunction of these processes in adipose tissue compartments is tightly linked to severe metabolic disorders, including obesity, metabolic syndrome, lipodystrophy, and cachexia. While numerous studies have addressed causes and consequences of obesity‐related adipose tissue hypertrophy and hyperplasia for health, critical pathways and mechanisms in (involuntary) adipose tissue loss as well as its systemic metabolic consequences are far less understood. In this review, we discuss the current understanding of conditions of adipose tissue wasting and review microenvironmental determinants of adipocyte (dys)function in related pathophysiologies. Abstract : This part of our Metabolism review series highlights both the physiological roles of adipose tissue and the pathological consequences of its dysfunction.